(untitled) (Research, Society and Development, 2020)
The present article reports a research carried out in the pedagogical political projects of the course of face-to-face math courses that are not likely to be extinct, in the state of Rio Grande do Sul, in a documentary study developed under a qualitative approach, with the objective of analyzing these projects with respect to Ethnomathematics. We believe that Ethnomathematics can be another significant device in the initial and continuing training of teachers, as well as a possibility to develop a contextualized teaching and learning process that values ​​the experiences of all involved. In the information collected, the incidence of the word Ethnomathematics was verified, identifying where and how many times the term occurred, also checking the context in which it occurred and analyzing the nomenclature of a curricular component of undergraduate courses, if in the bibliographies. basic or complementary throughout the Political Pedagogical Projects or else on the menu of some curricular component. We verified from the analysis of the research data, that in most of the researched degrees, Ethnomathematics is not very prominent, perhaps because it is still a little-known topic, naming only one curricular component in a single institution.